The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1093/qjmed/89.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA types A1-B8-DR3 and B27 with rapid and slow progression of HIV disease

Abstract: SummaryWe examined how HLA types A1-B8-DR3 and B27 were related to progression of clinical disease and rate of loss of CD4 lymphocytes in the Edinburgh City Hospital cohort of HIV-positive patients, mainly injection drug users. Patients (n = 692) were prospectively followed from 1985 through March 1994. Accurately estimated seroconversion times were determined retrospectively for a subgroup of 313 (45%). Of 262 patients (39%) who were fully or partially HLA typed, 155 (50%) had known seroconversions. Of 34 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 20 publications
5
67
0
1
Order By: Relevance
“…Several studies have shown (1) a temporal relationship between the decline of viral load and the emergence of CTL responses in both infected humans and infected monkeys, [3][4][5][6] (2) an increase of viral load after the appearance of CTL-escape HIV/SIV mutants during chronic and acute infection [7][8][9][10][11][12][13] and (3) a dramatic rise of viral load after CD8 þ T-cell depletion. [14][15][16] Additional indirect evidence for a CTL effect upon viral replication came from genetic association studies showing that Mhc class I alleles are strongly associated with survival time in HIV-infected humans [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown (1) a temporal relationship between the decline of viral load and the emergence of CTL responses in both infected humans and infected monkeys, [3][4][5][6] (2) an increase of viral load after the appearance of CTL-escape HIV/SIV mutants during chronic and acute infection [7][8][9][10][11][12][13] and (3) a dramatic rise of viral load after CD8 þ T-cell depletion. [14][15][16] Additional indirect evidence for a CTL effect upon viral replication came from genetic association studies showing that Mhc class I alleles are strongly associated with survival time in HIV-infected humans [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Pronounced differences in rates of progression to the acquired immunodeficiency syndrome (AIDS) and in survival exist amongst patients infected with the human immunodeficiency virus (HIV) [1][2][3][4]. A considerable proportion of the variation in progression rates will be due to factors which cannot be modified by medical interventions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent approaches have focused on vaccines capable of inducing potent CD8 ϩ T-cell responses to control the virus load, to reduce transmission, and to slow disease development (26,53). Evidence from both humans and nonhuman primates for the role of T-cell responses in the control of HIV includes the correlation between HIV-specific CD8 ϩ T cells and the control of plasma viremia (51,52,99); the association of certain restricting major histocompatibility complex (MHC) class I alleles, conserved T-cell epitopes, and slow disease progression (14,27,28,48,55,59,61,64,70,72,90,100); and the rapid increase in viral load after experimental CD8 ϩ lymphocyte depletion in simian immunodeficiency virus (SIV)-or simian-human immunodeficiency virus (SHIV)-infected rhesus macaques (2,54,86), providing a strong rationale for the development of T-cell-based vaccines. Recently the quality of the HIV-specific CD8 ϩ T cells associated with the control of HIV-1 virus loads in human long-term nonprogessors has been described, revealing characteristics of a polyfunctional profile simultaneously capable of degranulation and of producing gamma interferon (IFN-␥), interleukin-2 (IL-2), tumor necrosis factor alpha (TNF-␣), and macrophage inflammatory protein 1-␤ (9).…”
mentioning
confidence: 99%